Pemahaman Jama’ah Sema’an Al-Qur’an Jantiko Mantab tentang Banyu Barokah - Wahyudi Wahyudi (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
Phenomenon of community interaction with the Qur’an, in reality, has a varied and dynamic conception. The Jantiko Mantab community, for example, has a habit of putting water in the middle of reading the Qur’an. This water is called a Barokah Banyan nomenclature. But this often creates problems among puritans, because they are considered to have no clear argumentation in the perspective of syara ‘. So it needs a deep and comprehensive study of various aspects. The process of understanding the convergence of jama’ah semaan al-Qur’an Jantiko Mantab, seen from the perspective of the Berger & Luckman theory takes place through dialectical interaction of three forms of reality that become entry concepts, namely subjective reality, symbolic reality, and objective reality. The objective reality in the construction of the understanding of many baraka is the belief that the Qur’an is the source of baraka. From this Objective reality comes a symbolic expression of that belief (Symbolic reality) in the form of putting clear water in the Al-Qur’an. Individual understanding of the blessing of the Qur’an then interacts with the subjective reality of other individuals which then gives rise to an objective reality, in the form of banyu barokah. Fenomena interaksi masyarakat dengan al-Qur’an pada realitasnya memiliki konsepsi yang variatif dan dinamis. Komunitas Jantiko Mantab misalnya, memiliki kebiasaan meletakkan air di tengah-tengah pembacaan al-Qur’an. Air ini disebut dengan nomenklatur banyu barokah. Namun hal ini sering kali menimbulkan problematika di kalangan kaum puritan, karena dianggap tidak memiliki argumentasi yang jelas dalam perspektif syara’. Sehingga perlu kajian yang mendalam dan komprehensip dari berbagai macam aspeknya. Proses konstruksi pemahamaan jama’ah semaan al-Qur’an Jantiko Mantab, dilihat dari perspektif teori Berger & Luckman berlangsung melalui interaksi yang dialektis dari tiga bentuk realitas yang menjadi entry concept, yakni subjective reality, symbolic reality dan objective reality. Objective reality dalam konstruksi pemahaman banyu barokah adalah keyakinan bahwa al-Qur’an merupakan sumber barokah. Dari Objective reality ini muncul ekspresi simbolik dari keyakinan tersebut (Symblolic reality ) berupa meletakkan air bening dalam semaan al-Qur’an. Pemahaman individu akan barokah al-Qur’an kemudian berinteraksi dengan realitas subjektif individu- individu lain yang kemudian memunculkan satu Objective reality, berupa banyu barokah.